Meta-analysis of Information Technology Implementation in Libraries (Universitas Terbuka, 2024)
Technological developments have also changed the needs of library users significantly. Today's users want fast and easy access to information. In realizing this modernization of services, libraries must be able to adapt to current developments in information technology. This aims to ensure that libraries remain a valuable resource in the current digital era by designing better strategies to optimize the use of technology to improve the quality of services they have. Therefore, this research aims to find out a comprehensive picture of the application of information technology in various types of libraries in Indonesia. The method in this research uses meta analysis. Based on research, it is known that articles related to the application of information technology in libraries have been implemented in several types of libraries, namely in public, special, school and college libraries. However, it is most widely applied in college libraries. The majority of forms of application of information technology in libraries are in the form of library management systems, namely in the form of GPT chat, library websites, QR Baecode, RFID, OPAC, and SLiMS. These various applications of information technology have an impact on making work in the library more efficient and easier, as well as providing better services to library users.